Wading in the Covid-19 Pandemic: Fate and Ways Forward for Malaysian Creative Cities - Khoo, Suet Leng; Chang, Nicole Shu Fun (Journal of Urban Culture Research, 2023)
Since the 2019 Wuhan outbreak, the COVID-19 pandemic badly hit all sectors of the global economy. The creative and cultural sectors (CCS) are among the hardest hit. The value chain of CCS (i.e. creation, production, distribution, accessibility to contents) was severely immobilized. In cities, mitigation measures implemented to contain Covid-19 significantly downsized the CCS. Jobs, incomes and livelihoods of creative and cultural employees were threatened. These scenarios question the readiness, resilience and sustainability of CCS, particularly in cities. The fate and way forward of creative cities are now a grave concern. This paper aims to investigate the impacts, developments, reactions and policy responses of Malaysia’s CCS and creative cities as Covid-19 unfolds. Based on primary (i.e. interviews) and secondary data, three emerging Malaysian creative cities (i.e. Kuala Lumpur, George Town and Ipoh) were studied. The findings revealed that while government assistance is forthcoming, there is still room for inclusive policies from all tiers of governments and across diverse stakeholders (i.e. private, public, civil society) to reach out to creative employees who are socio-spatially segregated in Malaysia. It is also an opportune time to revisit and reinstate Malaysia’s CCS into national development given that these sectors were sidelined even before Covid-19.